Of love and evil [compact disc, unabridged] : the songs of the seraphim, a novel - Rice, Anne, 1941- (Random House Audio, 2010)
In fifteenth century Rome, Toby O'Dare, a recently retired government assassin, receives a visit from the angel Malchiah. The heavenly figure instructs O'Dare to solve a grisly murder. But during the investigation, O'Dare discovers that the city is being haunted by an ancient demon and that solving the murder may have disastrous consequences for all of Rome.